Analiza poškodb v slovenskem ženskem nogometu - Kutnjak, Manca (Šport (Ljubljana), 2021)
Women’s football has experienced a leap in development over the last decade. The quality of the game brings greater intensity and dynamics, which in turn means a higher incidence of injuries. Our goal was to analyze the type, location, and quantity of injuries in female players of different competitive levels and different playing positions. The sample consisted of 41 players who play in women‘s football clubs across Slovenia. To determine the differences between the groups of girls of national and international competition level and the differences between different playing positions (goalkeepers, defenders, midfielders, and strikers), we used the Chi-square test. Players of the international competition level and midfielders suffered the most injuries. The most injured parts of the body were the knee and ankle joint, and the midfielders also had many injuries to their fingers, wrists, and palms. Goalkeepers and strikers suffered the least injuries. Almost 50% of the girls surveyed do additional training outside of the regular club training process. The most common forms of training that female soccer players perform are strength and flexibility training on their own. In the future, more emphasis should be placed on the preventive exercise of the most damaged locations. In the case of younger football players, the basics of falls and rises should be included in the training programs, which could help reduce the incidence of injuries in the upper extremities.
Keywords: competition level; football; igralna mesta; injuries; nogomet; playing positions; poškodbe; sport; šport; tekmovalna stopnja; women; ženske